Tailoring Aerogel for Thermal Spray Applications in Aero-Engines: A Screening Study - Nadiir Bheekhun; Abd Rahim Abu Talib; Mohd Roshdi Hassan (Advances in Materials Science and Engineering)
Irregular silica aerogel particles had been tailored to a regular spherical shape within the proper granulometric size range for thermal spraying. Silica aerogel is an ultralow dense and highly porous nanomaterial with its thermal conductivity being the lowest than any solids. Although silica aerogels possess fascinating physical properties, their implementation is limited to aerogel-doped blankets in the aerospace industry. Due to space constraints, these heat insulative and fireproof blankets are not encouraged by aero-engine manufacturers, and hence, alternatives are being sought. Although it was thought that an aerogel-based thermally sprayed coating may be applicable, aerogel powders are extremely challenging to be injected and deposited by thermal spray guns because of their inappropriate granulometric and morphological properties. Consequently, this study intends to tailor the aerogel powders accordingly. Aerogel-based slurries with yttria-stabilized zirconia as a secondary ceramic were prepared and spray-dried according to a modified Taguchi experimental design in order to appreciate the effect of both the slurry formulation and drying conditions such as the solid content, the ratio of yttria-stabilized zirconia : aerogel added, the amount of dispersant and binder, inlet temperature, atomization pressure, and feeding rate on the aforementioned characteristics of the resulting spray-dried powder. Uniformity was found to be the most influenced one (F-ratio = 62.40) by the overall spray-drying process. Solid content had the most significant effect on median particle size (p value = 0.035) and volume fraction (p value = 0.010) but did not affect uniformity significantly (p value = 0.065). Furthermore, a strong positive and significant correlation existed (Pearson’s r = 0.930) between median particle size and volume fraction. Based on the derived relationships, an optimised condition to achieve the maximum median particle size was then predicted and verified experimentally. The optimised aerogel-based spray-dried powder had a median particle size, volume fraction, and uniformity of 28.93 ± 0.726 μm, 64.45 ± 0.535, and 0.475 ± 0.002, respectively. Finally, the morphology of the optimised powder was noticed to have been changed from irregular shapes to spherical or donut-like granules which made them within the frame of thermally sprayable. However, when the optimised spray-dried powder was weighed, the quantity was found to be 10% only from the total weight of ceramics within the slurry prior to spray-drying, which makes it uneconomically reasonable for subsequent thermal spraying.